The classification of the legal customs of the Ukrainian people: Historical-legal aspect - Marian Bedrii; Mariana Syrko (Wrocławsko-Lwowskie Zeszyty Prawnicze)
The article is devoted to the issues of analysing the legal significance of Ukrainian customs through the prism of various criteria which are not exhaustive but contributed to the systematization of knowledge about the Ukrainian customary law. In particular, the following criteria for the classification of legal customs are proposed: compliance with the legislation, the origin, nature of disposition, territorial distribution, sphere of legal regulation. The historical significance of legal customs based on the legal out- look of the Ukrainian people is revealed.